Атмосфералық ауа сапасын жақсарту бойынша шаралар кешені және ауа ортасының экологиялық мониторингі (Көкшетау қаласы мысалында) (ҚазҰУ хабаршысы. Экология сериясы, 2019)
Environmental monitoring of air quality is becoming increasingly important. The main part of cars has more than 10 years of age. Therebyrunning of these cars is more than 100 thousand kilometers and it meansthat ecological characteristics of most vehicles are equal to or exceed regulatory. The analysis of exhaust emissions toxicity showed that the vehiclesoperated in Kokshetau has emissions that are close to the maximum permissible. The use of additives and new fuels, traffic improving, car drivingoptimization and the development of alternative car designs will contribute to the normalization of air pollution of cities. The system of state control over air is intended to be the guarantor in the implementation of thesemeasures to improve environmental safety of vehicles.Key words: environmental monitoring, air quality condition, regulation of air quality, means of controlling toxic gases in the atmosphere, pollution, analysis, emissions, vehicle, operation of the engine.